2016
DOI: 10.1093/her/cyw009
|View full text |Cite
|
Sign up to set email alerts
|

Population-based evaluation of theLiveLighter’ healthy weight and lifestyle mass media campaign

Abstract: The Western Australian (WA) ‘LiveLighter’ (LL) mass media campaign ran during June–August and September–October 2012. The principal campaign ad graphically depicts visceral fat of an overweight individual (‘why’ change message), whereas supporting ads demonstrate simple changes to increase activity and eat healthier (‘how’ to change message). Cross-sectional surveys among population samples aged 25–49 were undertaken pre-campaign (N = 2012) and following the two media waves (N = 2005 and N = 2009) in the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 62 publications
2
69
1
Order By: Relevance
“…It is theorised that these observed changes in knowledge and behaviour with regard to sugary drink consumption are driven by the campaign simultaneously motivating , reinforcing and enabling adults to achieve health behaviour change . As reported previously, it is posited that individuals who perceive themselves to be susceptible will act to reduce their sugary drink consumption to the extent they are: motivated – determined by the personal perceived threat of not doing so (eg, disease, weight gain) and the extent to which the benefits of doing so are judged to outweigh the costs; enabled – determined by the belief one has the skills and ability necessary to reduce their sugary drink consumption; and reinforced – characterised by the extent to which results of reducing consumption are observable (eg, improved health, weight loss)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is theorised that these observed changes in knowledge and behaviour with regard to sugary drink consumption are driven by the campaign simultaneously motivating , reinforcing and enabling adults to achieve health behaviour change . As reported previously, it is posited that individuals who perceive themselves to be susceptible will act to reduce their sugary drink consumption to the extent they are: motivated – determined by the personal perceived threat of not doing so (eg, disease, weight gain) and the extent to which the benefits of doing so are judged to outweigh the costs; enabled – determined by the belief one has the skills and ability necessary to reduce their sugary drink consumption; and reinforced – characterised by the extent to which results of reducing consumption are observable (eg, improved health, weight loss)…”
Section: Discussionmentioning
confidence: 99%
“…To check for potential unintended campaign effects, respondents were asked whether they agreed or disagreed with five weight‐based stereotypes. Based on factor analysis, a composite scale combined ratings of “agreed” for two or more stereotypes . Respondents who reported they drank SSBs one or more times in the last week were classified as “weekly SSB consumers” and those who drank SSBs four or more times in the last week were classified as “frequent SSB consumers.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that programs targeting overweight and obesity, healthy eating and physical activity that have been introduced in recent decades are now beginning to bear some effect. For example, research has shown the LiveLighter campaign is associated with population‐level changes in physical activity intentions and in thoughts pertaining to the harmful effects of being overweight . There are many other high‐quality health promotion programs running in WA, and it is tempting to think that these might be starting to have an impact.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results from a public education campaign with a mass media component have been found in Australia with LiveLighter. The first phase of the campaign led to population‐level increases in knowledge of health harms related to weight gain . The second phase focused on consumption of sugary beverages and associated risk of weight.…”
Section: National Healthy Weight Strategymentioning
confidence: 99%